Determination of Infrared Drying Characteristics and Modelling of Drying Behaviour of Carrot Pomace - Doymaz, Ibrahim (ANKARA UNIV, FAC AGR, 2013)
In this study, drying characteristics of carrot pomace were determined and the applicability of different drying models was investigated in order to find the product's moisture content at any time of the drying process. Drying times of carrot pomace were found by drying at the infrared power levels of 83, 125, 167 and 209 W. It was observed that the power level affected the drying rate and time. To evaluate the drying kinetics of carrot pomace, the obtained experimental data were applied to twelve mathematical models and the model with the best fit was determined. According to the results, Aghbashlo et al model is superior to the others for explaining drying behavior of carrot pomace. Effective moisture diffusivity varied from 0.59 to 3.40x10(-10) m(2) s(-1) and was significantly influenced by infrared power. Activation energy was estimated by a modified Arrhenius type equation and found to be 5.73 kW kg(-1).
Keywords: Activation energy; Carrot pomace; Effective moisture diffusivity; Infrared drying; Mathematical modelling; MOISTURE DIFFUSIVITY; BY-PRODUCTS; LAYER; KINETICS; LEAVES; GRAPE; Agriculture